An Integrated Agency Approach to Mine Site Environmental Management and Control in New South Wales, Australia (The Australasian Institute of Mining and Metallurgy, 1995)
The Department of Mineral Resources is the lead agency in mine site environment management and control in New South Wales. The Department introduced a Mining, Rehabilitation and Environmental Management Plan (MREMP) process several years ago in order to integrate the activities of other government agencies who may have a material interest at the mine site. The MREMP process has resulted in a spirit of trust and co-operation between agencies and between agencies and mining companies. The spirit of co-operation has been reflected in greater public confidence that mining is environmentally responsible.